Maracas Bay - Sobrian, C. (Art Photo Studio, Trinidad, 2009)
Trinidad's popular Maracas beach where the people enjoy the sand and surf. The postcard is addressed to Mr. and Mrs. E.K. Uhler, Virginia, U.S. Affixed to the postcard are two Trinidad and Tobago stamps, a 2 cents and a 10 cents. Postcard has the number C-32940.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beachgoers--Trinidad and Tobago; Beaches--Trinidad and Tobago; Leisure--Trinidad and Tobago; Bays--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maracas Bay